2017
DOI: 10.1371/journal.pone.0184514
|View full text |Cite
|
Sign up to set email alerts
|

The cytoprotective protein clusterin is overexpressed in hypergastrinemic rodent models of oxyntic preneoplasia and promotes gastric cancer cell survival

Abstract: The cytoprotective protein clusterin is often dysregulated during tumorigenesis, and in the stomach, upregulation of clusterin marks emergence of the oxyntic atrophy (loss of acid-producing parietal cells)-associated spasmolytic polypeptide-expressing metaplasia (SPEM). The hormone gastrin is important for normal function and maturation of the gastric oxyntic mucosa and hypergastrinemia might be involved in gastric carcinogenesis. Gastrin induces expression of clusterin in adenocarcinoma cells. In the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 74 publications
1
11
0
Order By: Relevance
“…Gastric cancer is preceded by mucosal remodeling like spasmolytic polypeptide-expressing metaplasia (SPEM) and intestinal metaplasia. The cytoprotective protein clusterin (CLU) is highly expressed in oxyntic mucosa during the emergence of metaplasia, but it is unknown whether CLU promotes or counteracts the process 1, 2, 3, 4. Here, we use clusterin knockout (CLU-KO) mice to examine the role of CLU in the emergence, recovery, and repair of gastric metaplasia after tamoxifen-induced acute oxyntic atrophy 5 .…”
mentioning
confidence: 99%
“…Gastric cancer is preceded by mucosal remodeling like spasmolytic polypeptide-expressing metaplasia (SPEM) and intestinal metaplasia. The cytoprotective protein clusterin (CLU) is highly expressed in oxyntic mucosa during the emergence of metaplasia, but it is unknown whether CLU promotes or counteracts the process 1, 2, 3, 4. Here, we use clusterin knockout (CLU-KO) mice to examine the role of CLU in the emergence, recovery, and repair of gastric metaplasia after tamoxifen-induced acute oxyntic atrophy 5 .…”
mentioning
confidence: 99%
“…This showed that numerous genes previously reported to be associated with SPEM were overexpressed in KO/PEG versus WT/PEG mice, including tff2, clu, muc6, cd44 and wfdc2, with no significant change in KO mice receiving NTZ (Table 2). It was confirmed by both IHC and ISH that KO/PEG mice had pronounced expression of the SPEM markers TFF2 and clusterin in the gastric corpus [23] (Figures 3 and 4), and that the SPEM did not seem to be affected by NTZ. There was also overexpression of markers of intestinalizing transcripts such as cftr and muc4.…”
Section: Ntz Reduced Ne Cell Hyperplasia Whereas Spem Was Unaffectedmentioning
confidence: 66%
“…We have previously found that the SPEM marker clusterin is highly expressed in ECL cells of normogastrinemic rats, but in rats with hypergastrinemia due to PPI administration, clusterin expression was considerably increased, through a dominant shift in the expression towards cells of the mucous neck-chief cell lineages. [23]. Moreover, clusterin was found to be highly upregulated in mucus neck and SPEM cells of the H + /K + ATPase beta subunit KO mice of different ages [23].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations